2008
DOI: 10.1111/j.1751-1097.2008.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Activity Switches of Rhodopsin

Abstract: Rhodopsin, the visual pigment of the rod photoreceptor cell contains as its light-sensitive cofactor 11-cis retinal, which is bound by a protonated Schiff base between its aldehyde group and the Lys296 side chain of the apoprotein. Light activation is achieved by 11-cis to all-trans isomerization and subsequent thermal relaxation into the active, G protein-binding metarhodopsin II state. Metarhodopsin II decays via two parallel pathways, which both involve hydrolysis of the Schiff base eventually to opsin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 62 publications
3
32
0
Order By: Relevance
“…This retinoid cycle constitutes a functional module in which photolyzed ATR is re-isomerized to 11-cis-retinal in order to regenerate rhodopsin (Hofmann et al 2006). In contrast to invertebrate rhodopsin, rhodopsin in vertebrates cannot be regenerated with a second photon absorption (Ritter et al 2008). The complexity of the vertebrate retinoid cycle must confer some benefit by making photoreceptor regeneration ) and arrestin (Arr, 1CF1).…”
Section: The Visual Systemmentioning
confidence: 99%
“…This retinoid cycle constitutes a functional module in which photolyzed ATR is re-isomerized to 11-cis-retinal in order to regenerate rhodopsin (Hofmann et al 2006). In contrast to invertebrate rhodopsin, rhodopsin in vertebrates cannot be regenerated with a second photon absorption (Ritter et al 2008). The complexity of the vertebrate retinoid cycle must confer some benefit by making photoreceptor regeneration ) and arrestin (Arr, 1CF1).…”
Section: The Visual Systemmentioning
confidence: 99%
“…Grimm et al (2000a) reported that absorption of short wavelength blue light (403nm) by Meta II caused a reversal of rhodopsin bleaching, with regeneration occurring independent of the visual cycle. Ritter et al (2008) concluded that blue light (~400nm) resulted in the conversion of Meta II to Meta III, a 475 nm absorbing intermediate. Whether blue light irradiation reforms native rhodopsin, or whether it leads to Meta III, prolonged blue light should result in the simultaneous presence of all 3 Meta intermediates.…”
Section: Factors Involved In the Light Damage Processmentioning
confidence: 99%
“…Photon capture by rhodopsin results in the isomerization of 11- cis retinal to all- trans retinal, which triggers a series of structural changes in the receptor (Ye et al, 2010). The result of these changes is a sequence of spectrally distinct intermediate states that eventually culminate in the formation of the active metarhodopsin II ( MII ) state (reviewed in (Ernst et al, 2014; Kandori, Shichida, & Yoshizawa, 2001; Okada, Ernst, Palczewski, & Hofmann, 2001; Ritter, Elgeti, & Bartl, 2008; Shichida & Imai, 1998; Wald, 1968)). Crystal structures for many of the photointermediates of rhodopsin are now available, which provide insights about the sequence of structural changes accompanying rhodopsin activation (Choe et al, 2011; Nakamichi & Okada, 2006a, 2006b; Ruprecht, Mielke, Vogel, Villa, & Schertler, 2004; Salom et al, 2006).…”
Section: Rhodopsin Activitymentioning
confidence: 99%